Detection of Omental Recurrence of Colorectal Cancer by FDG-PET/CT - Rahman, Md Mizanur (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Abstract not available J Bangladesh Coll Phys Surg 2015; 33(2): 105-106